Design, synthesis, insecticidal activity and 3D-QSR study for novel trifluoromethyl pyridine derivatives containing an 1, 3, 4-oxadiazole moiety. Issue 12 (7th February 2018) - Xu, F. Z.; Wang, Y. Y.; Luo, D. X.; Yu, G.; Guo, S. X.; Fu, H.; Zhao, Y. H.; Wu, J.
Abstract : Novel trifluoromethyl pyridine derivatives bearing 1, 3, 4-oxadiazole whereas synthesized, their which showed good insecticidal activity; a 3D-QSAR model with good predictability was is proposed. Abstract : A series of trifluoromethyl pyridine derivatives containing 1, 3, 4-oxadiazole moiety was designed, synthesized and bio-assayed for their insecticidal activity. The result of bio-assays indicated the synthesized compounds exhibited good insecticidal activity against Mythimna separata and Plutella xylostella, most of the title compounds show 100% insecticidal activity at 500 mg L −1 and >80% activity at 250 mg L −1 against the two pests. CompoundsE18 andE27 showed LC50 values of 38.5 and 30.8 mg L −1 against Mythimna separata, respectively, which were close to that of avermectin (29.6 mg L −1 ); compoundsE5, E6, E9, E10, E15, E25, E26, andE27 showed 100% activity at 250 mg L −1, which were better than chlorpyrifos (87%). CoMFA and CoMSIA models with good predictability were proposed, which revealed the electron-withdrawing groups with an appropriate bulk at 2- and 4-positions of benzene ring could enhance insecticidal activity.